Analyzing Grammatical Errors in Student’s Conversation at Tahfidz Al-Quran Al-Amien Islamic Boarding School - Amini, Izzat; Rosa, S. Mailah (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
In the Arabic language, there are four skills that must be mastered for students and the skill of speak as one of the important skills in learning the Arabic language, and to increase the ability of students to speak Arabic, they must master in linguistic rules, especially grammatical rules. Therefore, the aim of this research is to analyze the grammatical errors in the conversation of third year students at the Tahfidz Al-Quran Al-Amien Islamic Boarding School. and the factors that cause them. The research method used by the researcher is a descriptive analysis. The researcher used the observation and interview method to collect the data, and in analyzing the data, the researcher used the method of condensing data, then presenting it, making inferences, and finally verifying it by the method of triangulation, that is, she used triangulation of the source. The results of this research were that the grammatical errors committed by female students were fifteen errors in words, sixteen errors in structure, and thirty-six errors in sentences. The factors that cause them are lack of interest in grammar, lack of understanding about grammar, neglect of grammar, the influence of the Indonesian language, and the traditions inherited from the old students in using the wrong language.